Strategi Kelompok usaha perempuan “SEPAKAT” dalam Pemberdayaan Perempuan Pesisir di Kabupaten Aceh Barat Daya - Mirawati Mirawati; Vellayati Hajad (Faculty of Social and Political Science, Universitas Siliwangi, 2022)
This study discusses the strategy of the Sepakat Group in empowering coastal women in Aceh Barat Daya District. The women's empowerment strategy is an effort to improve women's abilities, especially in developing their capacities and skills. This study uses a qualitative method using a case study approach, the data collection techniques used in this study are interviews and observations, the data collected is stored in one document and then selected according to research needs. The results showed that the women's empowerment strategy in Pulau Kayu Village, Southwest Aceh Regency needed attention and assistance from the government because there were still many obstacles and lack of understanding in improving the progress of the Agreed Women Business Group. The conclusion of this study shows that the strategy of the Women's Business Group Agrees on the Empowerment of Coastal Women in Aceh Barat Daya Regency is still weak due to the lack of attention from the local government on the progress of women's business groups agreeing on training and mentoring.